Frequency of Depression in Patients with Religious Inclination - Aman Ullah, Ghulam Hassan, Nauman Mazhar, Haider Khan (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To assess the frequency of depression in patients with religious inclination. Materials & Methods: It was a cross sectional survey conducted in outpatients’ department of Psychiatry of Sughra Shafi Medical Complex, Narowal over the period of 6 months. Sample size of 160 cases is calculated having age 40 to 75 years with 95% confidence level, 6% margin of error and taking expected percentage of depression was as 17% in subjects with religious inclination. Non-probability consecutive sampling was used. Depression was assessed according to HADS scale for depressive disorder of any severity. Results: Frequency of depression in patients with religious inclination was recorded in 19.38% (n=31) while 80.62% (n=129) had no findings of the morbidity. Conclusion: However, in observation of the above, we concluded that the frequency of depression in religiously inclined participants is not higher and some other factors i.e. socioeconomic was considerably greater, it may be the associated factor of depression in our study, further research in this field is necessary to validate our findings. Keywords: Depression, morbidity, religious inclination, socioeconomic status